2005
DOI: 10.1029/2004jd005111
|View full text |Cite
|
Sign up to set email alerts
|

A simple method to relate microwave radiances to upper tropospheric humidity

Abstract: [1] A brightness temperature (BT) transformation method can be applied to microwave data to retrieve Jacobian weighted upper tropospheric relative humidity (UTH) in a broad layer centered roughly between 6 and 8 km altitude. The UTH bias is below 4% RH, and the relative UTH bias below 20%. The UTH standard deviation is between 2 and 6.5% RH in absolute numbers, or between 10 and 27% in relative numbers. The standard deviation is dominated by the regression noise, resulting from vertical structure not accounted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(110 citation statements)
references
References 30 publications
(59 reference statements)
4
106
0
Order By: Relevance
“…Figure 13 shows brightness temperature histograms for the 183 ± 1 GHz channel on SSMIS, which is sensitive to upper tropospheric moisture (e.g. Buehler and John, 2005) and to deep convection (e.g. Hong et al, 2005).…”
Section: Results Over Landmentioning
confidence: 99%
“…Figure 13 shows brightness temperature histograms for the 183 ± 1 GHz channel on SSMIS, which is sensitive to upper tropospheric moisture (e.g. Buehler and John, 2005) and to deep convection (e.g. Hong et al, 2005).…”
Section: Results Over Landmentioning
confidence: 99%
“…We average the CPR IWP over the MHS pixel, and select a subset of collocations. For the collocations, only measurements that are within 20 degrees of the equator are used, in order to prevent a signal from the surface (Buehler and John, 2005). Only collocations where the MHS measurement is within 5 degrees of nadir are used, so that no significant limb effect occurs.…”
Section: Comparison Of Bt-iwp Relationsmentioning
confidence: 99%
“…The subset is restricted to pixels over ocean within 20 degrees of the equator, because a warm (and humid) atmosphere prevents the MHS from getting a signal from the surface (Buehler and John, 2005). Due to these restrictions, the neural network is only applicable to the tropics.…”
Section: Developing a Retrieval Using Neural Netsmentioning
confidence: 99%
“…The UTH retrieval method of Buehler and John (2005) was confirmed to be well suited for deriving a UTH climatology from AMSU-B Ch18 data. Also, some new light was shed on the known limitations of this method.…”
Section: Discussionmentioning
confidence: 90%
“…These channels have center frequencies of 183.31±1.00, 183.31±3.00, and 183.31±7.00 GHz and will be referred to as Ch18, Ch19, and Ch20, respectively. Recently, Buehler and John (2005) demonstrated that UTH can be derived from AMSU-B Ch18 brightness temperatures with a precision of 2% RH at low UTH values and 7% RH at high UTH values. The same retrieval algorithm was used for the work described here.…”
mentioning
confidence: 99%